2018
DOI: 10.21512/bbr.v9i2.4618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Marketing Implementation through Location Based Advertising on Customer’s Purchase Intention

Abstract: There were two objectives of the research, those were to find out the effects of Location Based Advertising (LBA) on customer’s attitude and purchase intention. Furthermore, this research sought the enhancement effect of timing in several features on the customer’s attitude toward LBA and purchase intention. The features used were the content appeal, interactivity, control, attitude toward advertising in general, customization, and intrusiveness. This research was a conclusive study with descriptive design. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
5
8
0
3
Order By: Relevance
“…Digital marketing is the most recent marketing tool commonly used for communication and promotion of services and products without limitation on time, location, and costs (Kim & Ko, 2012). Wibisurya (2018) revealed that digital marketing has a positive impact on purchase intention, with a major impact on attractive content, personalisation, and customisation for the consumer. Same goes for Poyurak and Softic (2019) who have shown a positive effect of digital marketing on purchase intentions through an exchange of opinions between consumers.…”
Section: Customer Relationship Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital marketing is the most recent marketing tool commonly used for communication and promotion of services and products without limitation on time, location, and costs (Kim & Ko, 2012). Wibisurya (2018) revealed that digital marketing has a positive impact on purchase intention, with a major impact on attractive content, personalisation, and customisation for the consumer. Same goes for Poyurak and Softic (2019) who have shown a positive effect of digital marketing on purchase intentions through an exchange of opinions between consumers.…”
Section: Customer Relationship Managementmentioning
confidence: 99%
“…Ahmed and Zahid (2014) claimed that CRM has a significant impact on purchase intention from customer care. Wibisurya (2018) on the other hand, mentioned that there is no general advertising to focus on new and personalised products for customers to get their attention to purchasing the new products. Henceforth, this study proposed the following hypothesis.…”
Section: H2: Digital Marketing Has a Significant Positive Impact On Crmmentioning
confidence: 99%
“…Although this study has combined variables that have never been studied in an integrated way before, the possibility to explore some gaps exist for future researchers. For example, to increase hotel purchase intention through an online website, digital marketing can be added as recommended by Wibisurya (2018) who concluded that Location-based Advertising (LBA) as part of digital marketing can create positive's customers' attitude towards purchase intention.…”
Section: Resultsmentioning
confidence: 99%
“…Aksesibilitas adalah ukuran kenyamanan atau kemudahan mengenai cara lokasi tata guna lahan untuk mendukung interaksi satusama lain dan mudah atau susahnya lokasi tersebut dicapai melalui sistem jaringan transportasi (Carvalho et al, 2016). Wibisurya (2018) berpendapat bahwa lokasi yang baik menjamin tersedianya akses yang cepat, dapat menarik sejumlah besar konsumen dan cukup kuat untuk mengubah pola berbelanja dan pembelian konsumen. Lokasi yang tepat dan strategis memudahkan akses bagi calon konsumen untuk memenuhi kebutuhannya.…”
Section: H2: Citra Merek Berpengaruh Terhadap Purchase Intentionunclassified
“…Diduga bahwa kekuatan merek Honda lebih mendorong orang memilihnya daripada kesulitan atau kemudahan akses menuju dealer, keterjangkauan juga diduga dapat diatasi dengan variasi ketersediaan moda transportasi di Kota Kendal. Temuan menyatakan accessibility bukan penyebab purchase intention, hasil penelitian ini tidak sesuai dengan penelitian yang dilakukan oleh Wibisurya (2018) Sosial value perception dinilai responden sebagai berikut: saya tidak akan membeli sepeda motor yang terlibat dalam suatu masalah 8,52, saya berpartisipasi aktif atau mendukung kegiatan sosial seperti memberikan mesin gratis kepada sekolah kejuruan 7,96, jika ada mode sepeda motor baru, saya akan membeli sepeda motor dengan mode yang baru 7,72, jika menggunakan mode sepeda motor baru dapat meningkatkan status dalam pergaulan sosial 7,69, jika ada model sepeda motor yang baru saya akan mencobanya 7,61. Hasil uji t variabel social value perception memiliki nilai probabilias 0,520 > 0,05.…”
Section: Pembahasanunclassified